THE IMPORTANCE OF THE FAMILY IN THE DEVELOPMENT OF THE COGNITIVE PROCESS OF CHILDREN WITH SPECIAL EDUCATIONAL NEEDS (American Journal of Interdisciplinary Research and Development, 2023)
The article describes the role and importance of the family in the development of the cognitive process of children with special educational needs, the issues studied in scientific sources, and the problems of their education.